Zachowania konsumenckie na rynku kawy ze szczególnym uwzględnieniem roli marki - Górska-Warsewicz, Hanna (Consumers Behaviour on Coffee Market with Special Attention Given to the Brand, 2005)
Brand is a special marketing tool associated with the process of company's identification, building the added value and achieving competitive advantage. The aim of this study is to analyse selected aspects of consumers' behaviour on coffee market with special attention given to purchase behaviour, perceived brand quality and brand loyalty. The empirical research was conducted in 2003 in the form of questionnaires with 200 coffee consumers in Warsaw and Warsaw area. On coffee market, the activity leading to the creation of loyalty and increase of the role of the brand concentrate on TV, press and radio advertising. It is related with well-known brands with high indices of perceived brand quality and high groups of consumers always purchasing the same brand.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 284-290